The Mechanical and Electrical Properties of Carbon Nanotube-Grafted Polyimide Nanocomposites - Lim, Jun; Shin, Dong Geun; Yeo, Hyeonuk; Goh, Munju; Ku, Bon-Cheol; Yang, Cheol-Min; Lee, Dong Su; Hwang, Jun-Yeon; Park, Byoungnam; You, Nam-Ho (WILEY-BLACKWELL, 2014)
Polyimide (PI)-based nanocomposites containing aminophenyl functionalized multiwalled carbon nanotubes (AP-MWCNTs) obtained through a diazonium salt reaction was successfully prepared by in situ polymerization. PI composites with different loadings of AP-MWCNTs were fabricated by the thermal conversion of poly(amic acid) (PAA)/AP-MWCNTs. The mechanical and electrical properties of the AP-MWCNTs/PI composites were improved compared with those of pure PI due to the homogeneous dispersion of AP-MWCNTs and the strong interfacial covalent bonds between AP-MWNTs and the PI matrix. The conductivity of AP-MWNTs/PI composites (5:95 w/w) was 9.32 x 10(-1) S/cm which was about 10(15) times higher than that of Pure PI. The tensile strength and tensile modules of the AP-MWCNTs/PI composites with 0.5 wt % of AP-MWCNTs were increased by about 77% (316.9 +/- 10.5 MPa) and 25% (8.30 +/- 1.10 GPa) compared to those of pure PI, respectively. (C) 2014 Wiley Periodicals, Inc.
Keywords: GRAPHENE; FILMS